The Impact of Improving Dermal Permeation on the Efficacy and Targeting of Liposome Nanoparticles as a Potential Treatment for Breast Cancer - Heba F. Salem; Amr Gamal; Haitham Saeed; Alaa S. Tulbah (MDPI AG, 2021)
Breast cancer is the most frequent malignancy in women. This work focuses on developing deformable liposomes as a potential carrier for breast cancer treatment and studying the impact of improving dermal permeation on the efficacy and targeting of liposomes. Raloxifene (RXF), an oestrogen antagonist, was used as a model drug. Using Box-Behnken design, different formulations of RXF-loaded deformable liposome (RLDL) were prepared using different propylene glycol, phospholipid and cholesterol concentrations. The percentage of entrapment efficiency (Y1), particle size (Y2), zeta potential (Y3) and steady-state flux (Y4) of the prepared formulations were all evaluated. Y1 and Y4 were significantly increased and Y2 and Y3 were significantly decreased when the propylene glycol concentration was increased. The optimization was obtained and the optimum formulation was that including phospholipid (1.40% w/w), cholesterol (0.15% w/w) and propylene glycol (10% v/v). The selected optimum formulation displayed a % EE of 78.34 ± 1.04% with a steady-state flux of 4.21 ± 0.02 µg/cm2/h. In order to investigate bioavailability, antitumor effectiveness and permeation, the optimum formulation was selected and included in a carbopol gel. The optimum gel formulation had 2.77 times higher bioavailability and, as a result, considerable antitumor action as compared to oral RXF. In conclusion, optimum RLDL gel may be an effective breast cancer treatment.